Development and evaluation of a target enrichment bait set for phylogenetic analysis of oomycetes. (4th July 2021) - Nguyen, Hai D. T.; McCormick, Wayne; Eyres, Jackson; Eggertson, Quinn; Hambleton, Sarah; Dettman, Jeremy R.
ABSTRACT: Target enrichment is a term that encompasses multiple related approaches where desired genomic regions are captured by molecular baits, leaving behind redundant or non-target regions in the genome, followed by amplification and next-generation sequencing of those captured regions. A molecular bait set was developed based on 426 single-copy, oomycete-specific orthologs and 3 barcoding genes. The bait set was tested on 27 oomycete samples (belonging to the Saprolegniales, Albuginales, and Peronosporales) derived from live and herbarium specimens, as well as control samples of true fungi and plants. Results show that (i) our method greatly enriches for the targeted orthologs on oomycete samples, but insignificantly on fungal and plant samples; (ii) an average of 263 out of 429 orthologs (61%) were recovered from oomycete live and herbarium specimens; (iii) sequencing roughly 100 000 read pairs per sample is sufficient for optimal ortholog recovery while maintaining low sequencing costs; and (iv) the expected relationships were recovered by phylogenetic analysis from the data generated. This is the first report of an oomycete-specific target enrichment method with broad potential applications for evolutionary and taxonomic studies. A key benefit of our target enrichment method is that it allows researchers to easily unlock the vast and unexplored oomycete genomic diversity stored in natural history collections.